Calculation and Analysis of Carbon Emissions in the Construction Industry of Zhejiang Province - Wang Hanyun; Tan Chen; Wang Tao; Wang Shengteng; Huang Jihua; Xu Hao (E3S Web of Conferences, 2023)
High rise buildings with large volume, high energy consumption, and high carbon emission base have become the focus of emission reduction work in public building types. The key issue of reducing carbon emissions throughout the entire lifecycle of high-rise buildings is how to predict their carbon emissions during the design phase, which is also a current research hotspot. As a developed province in southern China, Zhejiang bears important emission reduction tasks and responsibilities in the construction industry. This article applies the carbon emission factor method to calculate the carbon dioxide emissions in the construction sector of Zhejiang Province from 2005 to 2022. Based on Kaya’s identity, a carbon emission calculation model is established. Combined with scenario analysis method, the carbon emissions in the construction sector of Zhejiang Province from 2023 to 2060 are predicted and compared under different scenarios. The results show that under the scenario of technological breakthrough, the construction field can achieve the carbon peak goal by 2025, but in order to achieve the carbon neutrality goal by 2060, the existing energy conservation measures and carbon reduction technologies need to be strengthened.